Optimizing The Use of Cassava Plant and its Byproduct as Ruminant Feed - Risa Antari; U Umiyasih (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2009)
An alternative to overcome the lack of feed is to use local feed resources. Cassava (Manihot utilissima) is a tropical plant that grows easily in all types of soil. At the time of harvest, the price is relatively cheap. Cassava has a low nutritive value, especially in crude protein, but it is a potential source of energy. The research to optimize the use of cassava as feed is by enrichment of its nutritional value, production of single cell protein or supplementation with other feed ingredient. Cassava leaves or hay contain high protein level so that it can be used as protein source. However, its utilization is limited by anti nutritive compounds, such as cyanide acid and linamarin. It can be overcome by physical, chemical and biological treatments as detoxification. The use of cassava in livestock feed requires a formulation strategy to obtain the optimal productivity.   Key words: Byproducts, cassava, feed, cattle